A comprehensive review on structural behavior and mechanical performance of traditional timber joints in Patan durbar square - Aryal, Manish; Koirala, Sanket; Khadka, Shyam Sundar (Kathmandu University Journal of Science Engineering and Technology, 2025)
Traditional timber construction represents a critical element of Nepalese architectural heritage, integrating cultural craftsmanship with essential structural design. As Nepal lies within a highly seismically active region, the performance of timber joints, which connect primary structural members, becomes paramount, since joint failure frequently precipitates the collapse of entire buildings. This review systematically examines various traditional timber joints employed in the Patan Durbar Square area, including lap, scarf, finger, tongue-and-groove, mortise-tenon, and timber-masonry connections, synthesizing current research on their structural behavior. Non‑destructive on‑site observations within Patan revealed a predominant reliance on half‑lap joints for beam lengthening, stop‑bladed scarf joints with pegs to prevent longitudinal slippage, occasional finger joints in columns due to material constraints, and tongue‑and‑groove joints used where beam depths required adjustment. A critical finding from the inspection is the pronounced lack of uniformity in joint dimensions and geometries; rather than adhering to standardized engineering principles, these connections were crafted according to immediate construction needs and the available timber sizes. This inherent variability suggests that the joints were conceived primarily to facilitate construction and sustain vertical loads, not to resist the complex, multidirectional forces generated by seismic events. Consequently, while these traditional interlocking geometries perform adequately under gravity loads, they often lack the requisite stiffness, strength, and reliability to withstand strong ground shaking. Experimental data corroborate that the bending capacity of such jointed members is only a fraction (often less than 30-40%) of that of solid timber beams, rendering them particularly vulnerable in high‑moment regions. A thorough understanding of these geometric irregularities and mechanical limitations is therefore indispensable for engineers and conservators aiming to preserve these heritage structures while enhancing their resilience against future earthquakes through informed, scientifically‑grounded retrofitting strategies.